PELATIHAN PENGOLAHAN BIJI NANGKA MENJADI COOKIES DI KELOMPOK PEMBUAT DODOL DI SURANADI, LOMBOK BARAT - Ahmad Alamsyah; Eko Basuki; Dodi Handito; Siska Cicilia (Universitas Veteran Bangun Nusantara, 2023)
Jackfruit (Artocarpus heterophyllus Lamk) is a tropical fruit. The use of jackfruit is still limited so that people only consume the flesh of the fresh fruit. Unripe jackfruit is made warm and mixed with vegetables such as pecel and lodeh, while ripe jackfruit is made into syrup, dodol, chips, compote, pudding or eaten fresh. The by-product of these preparations is jackfruit seeds. It is only sold in the form of fresh seeds. The purpose of this activity was provide training on processing jackfruit seeds into cookies to partners, namely UD. Taste Kitchen in Suranadi, West Lombok. The stages of this service activity include surveys, discussions, training (transfer of technology for processing jackfruit seeds into cookies), and evaluation. The activity was held on Friday, September 23, 2022, involving 15 participants. Jackfruit seed flour is made at the Fatepa Food Processing Laboratory, Mataram University. Participants were given knowledge about the nutritional content of jackfruit seeds, types of processed jackfruit seeds, how to make flour, and how to make cookies made from jackfruit seed flour. It is hoped that from this activity, UD. Dapur Rasa and other dodol craftsmen can process jackfruit seeds into other products that have higher economic value.